The influence of different types of rest on football players` ability to repeat phosphagen exercise - Wolanski, P.; Zaton, M.; Murawska-Cialowicz, E. (Central European Journal of Sport Sciences and Medicine, 2016)
The aim of the study was to asses the influence of the type of rest on football players` ability to repeat a phosphagen exercise. Twelve football players from the Polish third league were involved in the study and were subjected to a maximum power test on a cycloergometer. Respiratory parameters, lactic acid concentration in capillary blood and acid-base balance parameters were registered before, during and after the test. The test was carried out twice. During the first test the subjects used an active rest break (A) and during the second one they used a passive rest break (B). In part A the quantity of relative work was 87.61 ±9.25 J/kg and in part B it was 78.5 ±6.58 J/kg (p = 0.012). In test A during exertion and during restitution (4th minute) we registered higher values of the respiratory parameters (Rf, VE, VO2, VO2/kg). Our conclusion is that passive rest should be used when the objective is the fastest resynthesis of PCr and ATP. An active rest break should be used when the goal is to remove the accumulated LA as soon as possible.